Differential content of vesicular glutamate transporters in subsets of vagal afferents projecting to the nucleus tractus solitarii in the rat. Issue 3 (15th February 2014) - Hermes, Sam M.; Colbert, James F.; Aicher, Sue A.
ABSTRACT The vagus nerve contains primary visceral afferents that convey sensory information from cardiovascular, pulmonary, and gastrointestinal tissues to the nucleus tractus solitarii (NTS). The heterogeneity of vagal afferents and their central terminals within the NTS is a common obstacle for evaluating functional groups of afferents. To determine whether different anterograde tracers can be used to identify distinct subpopulations of vagal afferents within NTS, we injected cholera toxin B subunit (CTb) and isolectin B4 (IB4) into the vagus nerve. Confocal analyses of medial NTS following injections of both CTb and IB4 into the same vagus nerve resulted in labeling of two exclusive populations of fibers. The ultrastructural patterns were also distinct. CTb was found in both myelinated and unmyelinated vagal axons and terminals in medial NTS, whereas IB4 was found only in unmyelinated afferents. Both tracers were observed in terminals with asymmetric synapses, suggesting excitatory transmission. Because glutamate is thought to be the neurotransmitter at this first primary afferent synapse in NTS, we determined whether vesicular glutamate transporters (VGLUTs) were differentially distributed among the two distinct populations of vagal afferents. Anterograde tracing from the vagus with CTb or IB4 was combined with immunohistochemistry for VGLUT1 or VGLUT2 in medial NTS and evaluated with confocal microscopy. CTb‐labeled afferents contained primarily VGLUT2 (83%), whereas IB4‐labeled afferents had low levels of vesicular transporters, VGLUT1 (5%) or VGLUT2 (21%). These findings suggest the possibility that glutamate release from unmyelinated vagal afferents may be regulated by a distinct, non‐VGLUT, mechanism. J. Comp. Neurol. 522:642–653, 2014. © 2013 Wiley Periodicals, Inc.